RUNOFF PRODUCTION AND EROSION PROCESSES ON A DEHESA IN WESTERN SPAIN* - Ceballos, Antonio; Cerdà, A.; Schnabel, Susanne (Geographical Review, 2010)
Runoff generation and soil erosion were investigated at the Guadalperal6n ex- perimental watershed (western Spain), within the land-use system known as dehesa, or open, managed evergreen forests. Season and type of surface were found to control runoff and soil- loss rates. Five soil units were selected as representative of surface types found in the study area: hillslope grass, bottom grass, tree cover, sheep trails, and shrub cover. Measurements were made in various conditions with simulated rainfall to gain an idea of the annual varia- tion in runoff and soil loss. Important seasonal differences were noted due to surface cover and moisture content of soil, but erosion rates were determined primarily by runoff. Surfaces covered with grass and shrubs always showed less erosion; surfaces covered with holm oaks showed higher runoff rates, due to the hydrophobic character of the soils. Concentrations of runoff sediment during the siniulations confirmed that erosion rates at the study site de- pended directly on the sediment available on the soil surface
Keywords: Dehesa; erosion; land use; rainfall simulation; runoff; Spain

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability

Analysis of rainfall trends and dry periods on a pluviometric gradient representative of Mediterranean climate in the Duero Basin, Spain - Ceballos, Antonio; Martı́nez-Fernández, José; Luengo-Ugidos, Miguel Ángel (Journal of Arid Environments, 2004)
The present work studies the trends in rainfall and the behaviour of dry spells along a pluviometric gradient representative of the conditions of the Mediterranean region. The region is characterized by a marked water deﬁcit in the summer, a pronounced irregularity in its rainfall regime, and a noteworthy frequency of dry spells or periods without appreciable rainfall. The results obtained conﬁrm the general previsions of the IPCC, with a predominance of dry years over wet ones and a negative rainfall trend in the central sector. An increase in intra-annual variability in rainfall, and a very pronounced occurrence of dry periods independent of the total annual rainfall, are also seen. These circumstances will potentially increase the vulnerability of several Mediterranean ecosystems located along the gradient that are currently subject to considerable pressure from human activities; this will increase the environmental problems of these zones (agro-forestry–grazing productivity, soil degradation, recharge of aquifers, forest ﬁres, runoff models, biological diversity and composition, etc.).
Keywords: dry spells; duero basin; Mediterranean ecosystems; rainfall gradient; rainfall variability

Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
The following values have no corresponding Zotero field: publisher: Elsevier
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget

Hydrological behaviour of a small catchment in the dehesa landuse system (Extremadura, SW Spain) - Ceballos, Antonio; Schnabel, Susanne (Journal of Hydrology, 1998)
Investigations of the hydrological processes operating in a small experimental catchment representative of the dehesa ecosystem were carried out. The dehesa constitutes a system of agro-silvo-pastoral landuse, which is characterized by a Mediterranean, semi-arid climate. The study includes an analysis of the relationships between rainfall, soil water content and discharge, as well as the establishment of the annual water budget. The results demonstrate a complex hydrological response. The relationships between the factors involved and the operating processes are difﬁcult to explain because of the decisive role played by the valley bottoms. These areas typically possess a sediment ﬁll, and contrast with the shallow soils developed on the hillslopes. Genesis and quantity of runoff (Hortonian or saturation) measured at the outlet depend on the antecedent moisture conditions of the valley bottoms because of their water-retention capacity. Annual runoff coefﬁcients are similar to those reported from other semi-arid areas. The analysis of the annual water budget shows that rainfall is positively related with both actual evapotranspiration and discharge
Keywords: Dehesa; Runoff–rainfall relationship; Semi-arid areas; Small catchment; Water budget

ESCORRENT~ A SUPERFICIAL EN LAS VERTIENTES DE UNA CUENCA HIDROGRÁFICA EN EL ECOSISTEMA DEHESA. CUENCA DE GUADALPERAL~ N - Ceballos, Antonio; Schnabel, S. (Geographicalia, 1997)
In a sinall catchrnent under tlie deliesa landuse system overland flow production on slopes is investigated. The obtained results show tliat tl-ie determination of tl-ie tlireshold value for tl-ie generation of runoff is complex. Total precipitation and rnaxim~~m intensity in 10 minutes are the principal factors that explain tl-ie production and generatioii of slope runoff
Keywords: dehesa ecosystem; overland flow; slopes

ESCORRENT~ A SUPERFICIAL EN LAS VERTIENTES DE UNA CUENCA HIDROGRÁFICA EN EL ECOSISTEMA DEHESA. CUENCA DE GUADALPERAL~ N - Ceballos, Antonio; Schnabel, S (Geographicalia, 1997)
In a sinall catchrnent under tlie deliesa landuse system overland flow production on slopes is investigated. The obtained results show tliat tl-ie determination of tl-ie tlireshold value for tl-ie generation of runoff is complex. Total precipitation and rnaxim~~m intensity in 10 minutes are the principal factors that explain tl-ie production and generatioii of slope runoff
Keywords: dehesa ecosystem; overland flow; slopes